The concept of "Ilmu' Pagkausug" in the Jawi materials from Sulu - Hairulla, Munap H. (Quezon City Tri-College, University of the Philippines Diliman, 2017)
"Ilmu' pagkausug, one of the living traditions of Sulu which has certainly played a vital role in the development of the Tausug society and culture is largely remained unexplored and unstudied. Ilmu pagkausug, which consists in spiritual knowledge as understood by the Tausug mukali seekers, serves interesting purposes. For example, it may protect the one who possesses it against bad spirits and fellow humans who may wish to harm them. The one who has that ilmu pagkausug is called "pagkausugan," which explicitly means a powerful, invincible and learned person. This ilmu' pagkausug is transmitted, practiced, possessed and preserved by the Tausug Mukali seekers in the Jawi written tradition of Sulu. Specifically, ilmuh pagkausug has the following aspects: 1) ilmu (the sacred words), 2) ma-ana sin ilmu iban dagbus sin ilmu (the meaning or description and understanding), 3) ammal (application of the ilmu or knowledge), 4) pag-usal sin ilmu (technique or secrets of the ilmu), and 5) the duwaa ilmu (prayer or spells asking the Divine power to intervene).
The study is guided by the following objectives: 1) to describe and explain the Tausug cultural concept of ilmu pagkausug; 2) to identify the ilmu pagkausug in the Jawi written tradition of Sulu; and 3) to determine the relevance of the ilmu pagkausug in Tausug society. Using Jawi tradition as the main source, the study aims at the following: 1) a broader appreciation and understanding of the Tausug Muslims as an ethno linguistic group; 2) the preservation of the Filipino Muslim heritage as part of the national heritage; and 3) the enrichment of the indigenous literature and its applications to academic discourse.
This study reveals that ilmu' pagkausug in the Jawi intellectual tradition of Sulu consists of the following: 1) panghati pa Tuhan iban parsugpatan kaniya (understandind God and our relationship with Him); 2) samabahayang or sumba pa Tuhan (worship or praises of God); 3) kasussihan or junub-istinjah (physical and spiritual purification of one's self); 4) dhikir (remembrance of God), 4)duwaa (supplication asking God's favor); and 4) the potent words or symbolic expressions written in Jawi scripts found in the pis siyulatan. To the mujkali seekers, these are fundamental components of the ilmu' pagkausug. In short, ilmu pagkausug in the Jawi material of Sulu is about knowledge on spirituality. This is the knowledge that the mukali seekers continue to search, preserve, and practice until they attain spiritual wellbeing, and ultimately become God's rahasiyah (closer to God) so they may earn Divine's favor for them to survive amidst hostile and dangerous environment surrounded them. In continuous search and practice of the ilmu' pagkausug, the seekers may develop the sense of tolerance, compassion, justice, humility, sacrifice, trustworthiness, dedication to the well-being of others and above all kasi-lasa, which are the basic elements and foundation of peaceful society.
Whether or not this ilmu' pagkausug is a mixture of pre-Islamic and Islamic elements, this study identified such spiritual knowledge as the essential component of the Tausug culture and society-the source of their inspiration, their hope, the cause for their bravery, and aspiration to rebuild a better nation in the future. In other words, ilmu pagkausug may serve or has served as a primary force for social progress, motivating individuals to develop spiritual qualities, and empowering them to strive for the betterment of their society"--Author.
Thesis
Keywords: Islam -- Philippines -- Sulu Archipelago; Muslims -- History -- Philippines -- Sources; Tausug (Philippine people) -- History -- Sources; Tausug language -- Texts